METODE SERVQUAL-SIX SIGMA UNTUK PENINGKATAN KUALITAS PELAYANAN PUBLIK (Studi Kasus di Kantor Kecamatan Kedungbanteng, Purwokerto) - Dian Andhika Prameswara; Mustafid Mustafid; Alan Prahutama (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Implementation public service is the fulfillment of civil rights that must be implemented by the government, so that its implementation must fit and be able to provide comfort and satisfaction for the society. Therefore, the performance of public services should be improved constantly and controlled so as to meet the needs of service users, because of the good and bad of a public service can be public benchmarks to assess the performance of the government. Measuring the quality of services is not as easy to measure the quality of the product, because the services are subjective. Therefore, the dimension of Servqual as a tool used to measure the performance of public services and Six Sigma to improve the performance of the public service. This study aims to apply the Servqual-Six Sigma methods with the aim to improve the performance of public services Kedungbanteng District Office. The results obtained in this study is that the dimensions of Servqual Six Sigma can be applied to improve the quality of public services.. As a whole, the results obtained indicate that the process of public service at the Kedungbanteng District Office not meet the standards of satisfaction targets 8. The process is based on the dimensions of Servqual is tangible, reliability, responsiveness, assurance, and empathy, respectively located in the sigma value 3,089; 3,102; 3,054; 3,195 and 3,219. This means, the number of mismatches that may arise from one million services performed for each dimension is respectively 5,61%; 5,46%; 6,01%; 4,5% and 4,28%. Keywords: Public service, Servqual, Six Sigma